Virtual microscopy in histological and histopathological teaching, an opportunity in dentistry. - Parra, Elizabeth (2022)
Virtual microscopy (VM) is being widely implemented in education and could lead to the replacement of light microscopy (LM). Objective: To provide a review of the literature based on the questions: What is the perception of academics and students? and What is the performance of students? regarding the teaching of histology and/or histopathology with VM in dentistry. Material and methods: The following databases were consulted: Pubmed, Scielo, Science Direct and Scopus, and 10 articles were selected. Results: All the studies that evaluated perception and academic performance obtained results in favor of VM. Conclusions: VM has a promising future, but more studies with similar methodologies and that consider the perception of academics are required.